Estrategias para el fortalecimiento del modelo de gestión en el distrito de salud N°23D02 de Santo Domingo de los Tsáchilas para el periodo 2015 - Morales De la Guerra, Marcia Maricela (2015)
The research paper entitled "Strategies for strengthening the management model in the Health District No. 23D02 of Santo Domingo de los Tsáchilas for the period 2015" project was born as an idea as this entity does not comply with the implementation of the Model 2012 Management implemented by the Ministry of Health, the Public Servants Act and neither the guidelines of the National Plan for Good Living. The stated goal in this research was: Devise strategies for strengthening the management model Nº23D02 Health District, the specific objectives outlined below: Conduct a situational analysis of the current District Health Directorate No. 23D02, produce an analysis SWOT and describe strategies for strengthening the management model, as an alternative solution to this investigation methods used are inductive, analytical, statistical to determine the most relevant conclusions; SWOT analysis shows between threats and weaknesses of the District Health Department No. 23D02 that officials do not meet the job profile and there is delay in work activities and delays in the process; well it was possible to see that they do not have trained personnel. Importantly, the institution has the support of Local Government and international institutions, plus surveys were conducted to officials of the institution and the most relevant questions according to the results resulted in 81% there is ignorance and failure model management. It is where the research to implement strategies that will enable the institution to comply with the Ministerial available 100% based on the management model implemented by the Ministry of Health in the different Coordination that make up the District Health Management Nº23D02 part. Key words: Strategies, Management Model, Management System